Emotional speech markers of psychiatric disturbance in Huntington’s disease - Chenain, Lucie; Fabre, Audrey; Titeux, Hadrien; Morgado, Graça; Youssov, Katia; Clavel, Chloé; Bachoud-Lévi, Anne-Catherine (Frontiers in Psychiatry, 2025)
IntroductionPsychiatric disorders and difficulties in emotional expression represent a major problem in the management of Huntington’s Disease (HD). To improve patient follow-up, we propose to investigate the link between emotional expression and psychiatric symptoms, measured by the Problem Behaviors Assessment (PBA) scale. To this aim we developed the first emotional/psychiatric speech corpus, emoHD.MethodsWe included 102 HD gene carriers and 35 healthy controls (HC). Psychiatric symptoms were assessed using PBA sub-scales for Depression, Irritability/aggressivity, Apathy, and Obsessive/compulsive symptoms. Speech was annotated using three emotional descriptors: primary emotions, affective phenomena, and activation levels. Affective phenomena labels were selected based on PBA statements by external participants unaware of the study’s aims. We analyzed (1) emotional descriptors’ relationships, (2) emotional expression differences between HD and HC, and (3) the associations between emotions and psychiatric symptoms.ResultsHD patients showed reduced emotional expressiveness than HC with more neutral activation levels (=0). Only the primary emotion “angry” was less expressed in HD compared to HC. In contrast they expressed more affective phenomena states like apathetic, confused, “depressed”, “disoriented”, “frustrated”, and “pessimistic” than HC, whereas they expressed less “other” and “irritable” than HC. Expressed emotions were congruent with psychiatric symptoms (e.g., “anxious” and “nervous” are positively associated with Depression PBA sub-scale; “frustrated” with Irritability/aggressivity PBA sub-scale).ConclusionWe showed that speech is a promising marker for emotional/psychiatric symptoms in HD, supporting future remote monitoring and personalized care strategies.